2016
DOI: 10.4194/1303-2712-v16_3_27
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The objective of this study was to investigate the effectiveness of plant extracts on the oxidative stability of n-3 rich fish oil emulsion. The antioxidant efficiency, water extracts of wild pistachio, rosemary and green tea, were evaluated in 10 % fish oil-in-water emulsions. The fish oil emulsion was oxidatively unstable as measured by fatty acid profile, peroxide and pAnisidine values and sensory analysis. Pre-emulsification of the fish oil with fish gelatin in water offered some protection towards oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Both extracts could be appropriate alternatives to synthetic antioxidants, having no additional limits to get optimal effects. Pourashouri et al ( 125 ) found that the concentrated aqueous extracts of wild pistacia, green tea, and rosemary extended the stability of a 10% fish oil-in-water emulsion for a few days.…”
Section: Application Of Plant Extract In Food Productsmentioning
confidence: 99%
“…Both extracts could be appropriate alternatives to synthetic antioxidants, having no additional limits to get optimal effects. Pourashouri et al ( 125 ) found that the concentrated aqueous extracts of wild pistacia, green tea, and rosemary extended the stability of a 10% fish oil-in-water emulsion for a few days.…”
Section: Application Of Plant Extract In Food Productsmentioning
confidence: 99%
“…Total phenolic content (TPC) was measured using the Folin-Ciocalteu method according to the procedure described by Pourashouri, Shabanpour, Abad and Zahiri (2016). The absorbance was measured at 725 nm.…”
Section: Antioxidant Properties Of Spirulina Extractmentioning
confidence: 99%